EFEKTIVITAS BUKLET EDUKASI TERHADAP PERILAKU DETEKSI DINI KANKER SERVIKS - Sri Wisnu Wardani; Rika Resmana; Sri Mulyati (Poltekkes Kemenkes Bandung, 2021)
The awareness of cervical cancer early detection behavior is still low because women not understand about benefits of cervical cancer detection tests. It needs to increase public awareness and be effective if supported by adequate media such as booklet. The purpose of this study was to analyze the effectiveness of the educational booklet on cervical cancer early detection behavior. This study used a quasi-experimental design. The research data was taken of 60 women of childbearing age (WUS) in the work area of ​​Puskesmas Ibrahim Adjie, Bandung City (30 WUS in the intervention group, 30 WUS in the control group). Data analysis using T test and Chi-Square test. The results showed that the educational booklet was effective in increasing the respondent's knowledge about cervical cancer early detection (p-value <0.005), 67.9% had a low level of knowledge, while the respondents with the knowledge level well, the majority (65.6%) underwent early detection of cervical cancer. There is a relationship between knowledge level and cervical cancer early detection behavior (p-value <0.005, OR 4.03). From the group of respondents who read the booklet, 63.3% did early detection of cervical cancer, and vice versa, most of the respondents who did not read the booklet did not do early detection of cervical cancer. (63.3%). There is a relationship between educational booklets and cervical cancer early detection behavior (p-value = 0.039, OR 2.98)